Soil saline-alkali heterogeneity is an important factor driving the spatial expansion of clonal plant in grassland - Qu, Luhao; Liu, Jun; Yang, Jiyun; Bai, Long; Huang, Yue; Lu, Nan; Yu, Hongzhu; Wang, Zhifeng; Li, Zhonghe (Frontiers in Environmental Science, 2023)
Soil salinity is well known heterogeneous and various within natural soil environment. In Songnen grassland of Northeast China, grazing aggravates the saline-alkali heterogeneity in soil habitat, which led to dominant clonal plant species forming a variety of adaptive strategies. However, based on the previous studies of morphological plasticity and clonal integration in clonal plants, there was a lack of mechanism research on the spatial expansion strategy of clonal plants population subjected to clipping in saline-alkali heterogeneity soil patches. To address this knowledge gap, we carried out an experiment by applying different clipping intensities (0%, 35%, 70% of the above-ground biomass removed) to explore the spatial expansion strategy and morphological plasticity of Leymus chinensis and their belowground rhizomes in different heterogeneous saline-alkali patches. We found that, clipping significantly decreased the plant average height and above-ground biomass in homogeneous patches, especially heavy clipping had a significant adverse impact on plant belowground (rhizome, fine root) biomass and leaf area. However, there was no significant difference in the biomass, average height, and leaf area among the clipping treatments in low saline-alkali heterogeneous patches. In addition, the number of leaves, daughter plants and rhizome internode buds were significantly affected by saline-alkali heterogeneity alone, and low saline-alkali heterogeneity had a positive effect on these parameters. Biomass accumulation and rhizome expansion were gradually inhibited by the increasing of clipping intensity in a homogeneous environment, but the inhibitory effect of clipping was not significant in saline-alkali patches soil. We concluded that L. chinensis can respond to grazing or mowing disturbance by increasing tiller and daughter-plant numbers in a saline-alkali heterogeneous environment. The saline-alkali patches promoted clonal plant population spatial expansion more than grazing or mowing disturbance did. This study emphasizes saline-alkali heterogeneity distribution patterns in grassland soil environment were the primary and important driving factor promoting the spatial expansion of L. chinensis.